2023
DOI: 10.1049/cdt2.12053
|View full text |Cite
|
Sign up to set email alerts
|

Fast approximation of the top‐k items in data streams using FPGAs

Abstract: Two methods are presented for finding the top-k items in data streams using Field Programmable Gate Arrays (FPGAs). These methods deploy two variants of a novel accelerator architecture capable of extracting an approximate list of the topmost frequently occurring items in a single pass over the input stream without the need for random access. The first variant of the accelerator implements the well-known Probabilistic sampling algorithm by mapping its main processing stages to a hardware architecture consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Each PE contains a small independent memory allocated for updating a single or small number of key-value tuples [9]. A limited number of such systolic array accelerators have been specifically designed to compute the heavy hitters in data streams [10][11][12][13]. Most of these accelerators implement the popular Space-Saving algorithm [14].…”
Section: Fpga Implementations Of Counter-based Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each PE contains a small independent memory allocated for updating a single or small number of key-value tuples [9]. A limited number of such systolic array accelerators have been specifically designed to compute the heavy hitters in data streams [10][11][12][13]. Most of these accelerators implement the popular Space-Saving algorithm [14].…”
Section: Fpga Implementations Of Counter-based Algorithmsmentioning
confidence: 99%
“…Current Space-Saving FPGA implementations can be used to monitor hundreds to a few thousands of items using mid-capacity and large-capacity FPGA chips [11][12][13]. The work in [10] showed that the Probabilistic sampling algorithm proposed in [8] maps better to a systolic array architecture, resulting in some notable improvements compared to Space-Saving.…”
Section: Fpga Implementations Of Counter-based Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations